THE EFFECT OF TAX PLANNING, DEFERRED TAX EXPENSE AND CURRENT TAX EXPENSE ON PROFIT MANAGEMENT - Usi Sulistiawati; Prima Sadewa (Journal Informatic, Education and Management (JIEM), 2026)
This study aims to examine the effect of tax planning, deferred tax expense, and current tax expense on earnings management in food and beverage sub-sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. This research employed a quantitative approach with an associative research design. The data used were secondary data obtained from the annual financial statements of food and beverage sub-sector companies listed on the Indonesia Stock Exchange. The sampling technique applied was purposive sampling, resulting in 10 companies with a total of 50 observations during the research period. Data were analyzed using panel data regression with the assistance of EViews 12 software. The findings reveal that tax planning, deferred tax expense, and current tax expense simultaneously have a significant effect on earnings management. Partially, tax planning has a significant effect on earnings management. Deferred tax expense also has a significant effect on earnings management. Likewise, current tax expense has a significant effect on earnings management. These findings indicate that tax planning, deferred tax expense, and current tax expense are important determinants of earnings management practices in food and beverage sub-sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period.